Tata Kelola Dokumen Rekam Medis Sebagai Upaya Menjaga Rahasia Medis di Pelayanan Kesehatan - Judi Judi; Kusuma Estu Werdani; Salma Binti Purwaningsih; Purwanti . (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
The purposes of this study are To know the barriers and solutions in the management of medical record documents as an effort to keep the medical secrets in health care unit. Research method used in this study is empiricalnormativejuridical, by using secondary data consists of primary legal materials, secondary legal materials, tertiary legal materials, and primary data as supporting data. This research uses descriptive analytical. The results of this study are; 1) Medical secrets are the patient's right which much be protected and upheld by all health care providers. 2) Violation of the rights of these patients is a crime that can be sued by the law. The barrier found in this research is in reality, many hospitals are lack of medical records staffs to manage the medical documents. The solution to this problem is to build health care partnership that puts the health providers and the health receivers in a partnership. The suggestion is the health care providers should hire professional medical record staffs for keeping the medical secrets.